The Role of Foramen Magnum Morphometric Measurements in Assessing Human Demographic Parameters: A Narrative Review - Piyush Kant; Dr. Monu Sarin; Santosh Kumar; Dharavath Naveen; M. Naga Theja (The Bioscan, 2026)
Foramen magnum morphometry has been explored as a potential tool for demographic assessment in forensic, anatomical, and radiological fields. Nonetheless, differences in methodology and the characteristics of populations limit the ability to apply findings consistently.